Tantangan Perbankan Syariah Dalam Pemberdayaan UMKM Di Indonesia - Shodiq, Ricky Jafar; Mubarok, Ahmad Fauzan (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Sharia banking is one of the banks that is popular with the Indonesian people because it uses Islamic principles. This makes it easier for customers to carry out transactions with sharia banks. However, with changing times and government regulations regarding 12% VAT, of course, it presents a new challenge for Islamic banks in empowering MSMEs. This research aims to determine the challenges of Islamic banking in empowering MSMEs in Indonesia and at the same time provide solutions to overcome these challenges. The research method used in this research is literature study. The research results show that changing VAT to 12% has an impact on Islamic banks in empowering MSMEs because business people are concerned about the price of goods production. Sharia banks also need to make improvements in application access to make it easier to keep up with changing times and make transactions easier for customers. Proper empowerment and education for MSMEs carried out by Islamic banks will have a good impact on MSME players.